Education-occupation mismatch: is there an income penalty? - Martin Nordin; Inga Persson; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2008)
This paper adds to the small literature on the consequences of education-occupation mismatches. It examines the income penalty for field of education-occupation mismatches for men and women with higher education in Sweden and reveals that the penalty for such mismatches is large for both men and women. In fact, it is substantially larger than has been found for the US. Controlling for cognitive ability further establishes that the income penalty is not caused by a sorting by ability, at least for Swedish men. The income penalty for men decreases with work experience which is an indication that education-specific skills and work experience are substitutes to some extent. There is no evidence, though, that the mismatched individuals move to a matching occupation over time. Thus, for some, the income penalty seems to be permanent.
urn:nbn:de:101:1-20081126811
Keywords: I21; 330; Human capital; rate of return; salary wage differentials; educational economics; Humankapital; Anforderungsprofil; Lohnstruktur; Bildungsertrag; Schweden